Advances in electrospinning: The production and application of nanofibres and nanofibrous structures. Issue 3 (2nd July 2016) - Mokhtari, F.; Salehi, M.; Zamani, F.; Hajiani, F.; Zeighami, F.; Latifi, M.
ABSTRACT: The use of electrospun nanofibres in applications such as medical products, fuel cells, photocatalysis, filtration, sensors and actuators is reviewed. Yarn production is classified into two types, namely hollow and core-shell structures; the methods used for producing the two structures for different polymers are discussed. Explanations are given for the various arrangements for producing nanofibre yarns and bundles in non-twisted or twisted forms to suit their end use. Natural and synthetic polymer products for biomedical uses and their applications in the form of polymer nanofibres are reviewed and polymeric optical fibres for use in photonic devices and optical circuits are evaluated. The production and development of nanofibrous filtration devices is explored with specific reference to water treatment and the control of air pollution. Particular attention is then given to the evaluation of different electrospinning methods for PVDF (polyvinylidene fluoride), a piezoelectric polymer widely used in sensor applications in terms of their ability to harvest more energy after agitation of the sensor and the effects of different additives on the piezoelectric properties of PVDF. Priorities for further research are then outlined.